1971
DOI: 10.1083/jcb.49.3.722
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES OF MEMBRANE FORMATION IN TETRAHYMENA PYRIFORMIS

Abstract: When 1 1 4C-palmitic acid is used to pulse label logarithmic cultures of Tetrahymena pyriformis, radioactivity appears in lipids of the various membrane types at vastly differing rates . The microsomes and postmicrosomal supernatant attain a high specific radioactivity within 1 min, while the membranes enveloping the cilia require several hours to reach the microsomal level . A similar pattern is obtained when the tracer is sodium 11 4 0-acetate or 8,9 8H-hexadecyl glycerol . In all fractions the phosphonolipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, as additional time elapsed following administration of the isotope, its relative distribution in cilia changed, so that the radioactivity was eventually apportioned in just the same pattern as is the mass of the lipids. One example of this changing lipid distribution pattern in cilia and other membrane fractions was presented earlier (Nozawa and Thompson, 1971b). Graphing the radioactivity in the three major phospholipids of palmitate-l4C-labeled cells revealed that in cilia (and, to a much lesser degree, in all other fractions) there was a gradual rise in the relative 4444 BIOCHEMISTRY, VOL.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…However, as additional time elapsed following administration of the isotope, its relative distribution in cilia changed, so that the radioactivity was eventually apportioned in just the same pattern as is the mass of the lipids. One example of this changing lipid distribution pattern in cilia and other membrane fractions was presented earlier (Nozawa and Thompson, 1971b). Graphing the radioactivity in the three major phospholipids of palmitate-l4C-labeled cells revealed that in cilia (and, to a much lesser degree, in all other fractions) there was a gradual rise in the relative 4444 BIOCHEMISTRY, VOL.…”
Section: Resultsmentioning
confidence: 68%
“…Evidence pertinent to this question has been obtained by extending previous observations on the intracellular redistribution of radioactive lipids (Nozawa and Thompson, 1971b).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Antibodies to surface components of T. thermophila were prepared by immunising rabbits subscapularly with an emulsion of pellicles (prepared according to [6]) in complete Freunds adjuvant. Boosting injections were administered in weeks 3 and 7.…”
Section: Methodsmentioning
confidence: 99%